Social contact, practice, organization and technical knowledge: Experiences of music students in the course of the COVID-19 pandemic - Spahn, Claudia; Immerz, Anna; Hipp, Anna Maria; Nusseck, Manfred (Frontiers in Psychology, 2022)
For music students, the COVID-19 pandemic has had a great impact, forcing them to adapt to certain coronavirus regulations laid down by the state. In this study, the experiences of music students in three consecutive semesters under different coronavirus-related conditions are investigated. At the end of three semesters, the lockdown semester [SS (Summer Semester) 2020: April – July], a partially opened semester [WS (Winter Semester) 2020/21: October – February] and a mostly opened semester (SS 2021), a total of 152 music students at the University of Music Freiburg were asked to fill in an online survey. A mixed-methods approach was used, with results showing that the qualitative statements of the students support the quantitative data. The results of the cross-sectional study demonstrate that self-regulated learning improved during the lockdown semester, through new time management and focused practice with regular breaks. During the partially opened semester, the use of blended learning formats led to organizational problems, such as travel time and change of locations. Furthermore, music students were challenged by the social distancing, which improved during the partially opened, and mostly opened semester. New technologies regarding digital communication formats were emerged, which have evolved over the course of the three semesters. Concerning the overall experience, students stated that the partially-opened semester was most challenging, since distances and change of locations had to be combined with quickly changing public COVID-19-regulations. These findings during different stages of the COVID-19 pandemic provide constructive starting points for future teaching.